A 10-Year Trend Analysis of Heart Failure in the Less Developed Brazil - Fernandes,Amanda D. F. (2020)
Abstract Background: Data on heart failure (HF) epidemiology in less developed areas of Brazil are scarce. Objective: Our aim was to determine the HF morbidity and mortality in Paraiba and Brazil and its 10-year trends. Methods: A retrospective search was conducted from 2008 to 2017 using the DATASUS database and included patients ≥ 15 years old with a primary diagnosis of HF. Data on in-hospital and population morbidity and mortality were collected and stratified by year, gender and age. Pearson correlation and linear-by-linear association test for trends were calculated, with a level of significance of 5%. Results: From 2008 to 2017, HF admissions decreased 62% (p = 0.004) in Paraiba and 34% (p = 0.004) in Brazil. The in-hospital mortality rate increased in Paraiba and Brazil [65.1% (p = 0.006) and 30.1% (p = 0.003), respectively], but the absolute in-hospital mortality had a significant decrease only in Paraiba [37.5% (p = 0.013)], which was maintained after age stratification, except for groups 15-19, 60-69 and > 80 years. It was observed an increase in the hospital stay [44% (p = 0.004) in Paraiba and 12.3% (p = 0.004) in Brazil]. From 2008 to 2015, mortality rate for HF in the population decreased 10.7% (p = 0.047) in Paraiba and 7.7% (p = 0.017) in Brazil. Conclusions: Although HF mortality rate has been decreasing in Paraiba and Brazil, an increase in the in-hospital mortality rate and length of stay for HF has been observed. Hospital-based clinical studies should be performed to identify the causes for these trends of increase.